Research on Spatio-Temporal Complexity Evolution and Influencing Factors of “Nongrain” in Guangxi - Chongzhen Tang; Yongyi Yi; Yani Kuang (Discrete Dynamics in Nature and Society)
The “nongrain” problem of farmland has an important influence on grain production safety and planting structure stability in China. Using statistical analysis and spatial analysis tools to explore the spatial and temporal distribution characteristics of “nongrain” cultivation trend in Guangxi, and through the geographically weighted regression model to analyze the factors affecting the degree of “nongrain” cultivation trend in Guangxi. The results showed that (1) the proportion of nongrain crops in Guangxi was increasing from 2009 to 2019, and the decrease of rice planting areas and the increase of vegetable planting area were the main reasons for the trend of “nongrain” in Guangxi. (2) the proportion of oil crop planting area increased rapidly in northwest Guangxi, and the overall growth rate was faster in 2009–2014. The proportion of vegetable planting area increased rapidly in the western and central regions, and the overall growth rate was faster in 2014–2019. The proportion of sugarcane and cassava planting area showed a downward trend in most regions, and the sugarcane decreased significantly in the northwest and eastern regions. (3) The effect of urbanization rate on the degree of “nongrain” is positive in southern Guangxi and negative in northern Guangxi. The average annual temperature is positively correlated in the north and negatively correlated in the south. Agricultural population and average annual precipitation are positively correlated in all regions and are the most significant in the northeast and the north, respectively. The ratio of grain production to sowing and the total power of agricultural machinery are negatively correlated in most areas and are most significant in the northeast. Finally, based on the research conclusion, this study puts forward some policy suggestions for preventing “nongrain” and stabilizing grain production in China.